Architecture as a Human Right Matter - Nooraddin, Hoshiar (Advances in Social Sciences Research Journal, 2015)
The history is crowded with destruction of cities and their architecture following wars and conflicts. As a consequence, large number of architectural cultures had been removed from the earth or ended as ruins. Unfortunately, this problem is not only from the past but it is also taking place in the present civilized age. This paper is building on case studies to show how this phenomenon is rooted in the history and which consequences it has into the continuity of the local architecture in forming the present built environment. The case studies are historical evidences-based explanation, prediction and theory about the extent to which elite groups or dominating ethnical groups contribute to form the architecture of the multi-ethnic countries. The study’s evidences show the necessity of finding solutions for this problem in education, decision making and applied projects. To make the solution sustainable, the study is suggesting considering the architecture as a human right for all ethnical groups. Such shift can help us to secure all nations’ architecture as human resources for present and future generations